Comparation between the Bricker ileal conduit vs double-barrelled wet colostomy after pelvic exenteration for gynaecological malignancies. (March 2023) - Lago, Víctor; Pradillo Aramendi, Tamara; Segarra-Vidal, Blanca; Padilla-Iserte, Pablo; Matute, Luis; Gurrea, Marta; Pontones, José Luis; Delgado, Francisco; Domingo, Santiago
Highlights: Double-barrelled wet colostomy presents advantages like the single stoma placement and the simplicity of the technique. There are no differences in the rate of complications between double-barrelled wet colostomy and Bricker ileal conduit. The long-term complications related to urinary diversion remain high despite the type of technique. The DFS and OS after 48 months of follow up was 51 % and 58 % respectively. Abstract: Background: After exhausting other therapeutic options, pelvic exenteration is performed in patients who suffer from relapsed gynaecologic tumours, with most of them requiring some sort of urinary diversion. Material and methods: The main objective of this study was to assess the short- and medium/long-term urinary complications associated with the Bricker ileal conduit versus double-barrelled wet colostomy after performing a pelvic exenteration for gynaecologic malignancies. Results: A total of 61 pelvic exenterations were identified between November 2010 and April 2022; 29 Bricker ileal conduits and 20 double-barrelled wet colostomies were included in the urinary diversion analysis. Regarding the specific short-term urinary complications, no differences were found in the rate of urinary leakage (3 vs 0 %; p = 1), urostomy complications (7 vs 0 %; p = 0.51), acute renal failure (10 vs 20 %; p = 0.24) or urinary infection (0 vs 5 %; p = 0.41). Up to 69 % of patients with Bricker ileal conduits and 65 % of double-barrelled wet colostomies (p = 0.76) presented specific medium/long-term urinary complications. No differences in the rates of pyelonephritis (59 vs 53 %; p = 0.71), urinary fistula (0 vs 12 %; p = 0.13), ureteral stricture (10 vs 6 %; p = 1), conduit failure and reconstruction (7 vs 0 %; p = 0.53), renal failure (38 vs 29 %; p = 0.56) or electrolyte disorders (24 vs 18 %; p = 0.72) were found. Conclusions: There are no significant differences in the rate of complications between double-barrelled wet colostomy and the Bricker ileal conduit. The long-term complications related to urinary diversion remained high regardless of the type of technique. In this context, the double-barrelled wet colostomy presents advantages such as the single stoma placement and the simplicity of the technique.